THE INFLUENCE OF STORE ATMOSPHERE AND PRICE ON PURCHASING DECISIONS - Eko Putra; Kasman Karimi; Mardahleni, Mardahleni; Wildan, Wildan (Ikatan Dosen Menulis, 2025)
This study aims to determine and analyze the influence of store atmosphere and price on purchasing decisions (a study of consumers at Takana Juo Tiku Restaurant). This study uses a quantitative method with a descriptive approach. The population in this study is all customers of Takana Juo Restaurant. The sampling method used is non-probability sampling, which means not giving equal opportunities or chances to each member of the population when being selected as a sample. While the technique used in this method is purposive sampling, a sampling technique with certain considerations or criteria, namely consumers who have eaten at Takana Juo Restaurant. The number of samples in this study was 150 samples. The results of the study found that: The Store Atmosphere variable has a positive and significant effect on purchasing decisions with a coefficient value of 0.558, a t-value of 7.280 and a significant value of 0.000 (<0.05). The Price variable has a positive and significant effect on purchasing decisions with a coefficient value of 0.279, a t-value of 3.952 and a significant value of 0.000 (<0.05). The independent variables simultaneously have a positive and significant effect on purchasing decisions, with a regression coefficient of 103.407 at a significance level of 0.000 (<0.50). The coefficient of determination is 58.5%. The remaining 41.5% is influenced by other variables not included in this study.